(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the philosophical interpretation of the concept of social justice, tracing its historical evolution and analyzing its modern conceptualizations. The ideas ofprominent thinkers such as Plato, Aristotle, Al-Farabi, Ibn Sina, John Rawls, and Amartya Sen are examined in order to highlight various perspectives on justice. Particular attention is paid to the understanding of social justice within the sociophilosophical context of contemporary Uzbekistan, where the concept is analyzed in relation to national values and ongoing social reforms. The article seeks to provide a deeper philosophical insight into the role of social justice in achieving societal stability and sustainable development.